HUBUNGAN TEKNIK PERLEKATAN MENYUSUI DENGAN KEJADIAN REGURGITASI PADA BAYI USIA 0-2 BULAN - Yovia Rahayu; Riri Novayelinda; Agrina Agrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Latch-on technique is important aspects that determine the success of breastfeeding. Latch-on technique can increase the comfort of the baby while breastfeeding and decrease breastfeeding problems. The aim of this research was to identify the relationship of breastfeeding latch-on technique towards the regurgitation incidence among 0-2 months infant. The design was descriptive correlational research with cross sectional approach. The sampling technique purposive sampling involving 34 breastfeeding mother who have babies 0-2 month in Puskesmas Harapan Raya, that was selected based on inclusion criteria. This research used observation sheet adopted from LATCH Score that already tested for validity and reliability. This research using univariate and bivariate analysis with chi-square test with alternative test using hipotesis komparatif kategorik test. The results of this study indicate that 17 respondents (50%) showed breastfeeding latch-on techniques in good categories during observation, while the rest in the less good categories. As many as 19 respondents (55,9%) who experienced regurgitation. The results showed that p value was 0,000 (p value< 0,05), which means that there is a relationship between breastfeeding latch-on technique towards the regurgitation incidence among 0-2 months infant. Based on the results of this study is expected to the public, especially mothers who have babies properly and pay attention to the technique of latch-on breastfeeding to avoid health problems, especially the incidence of regurgitation. Keywords: Early infant, Latch-on techniques, LATCH Score, Regurgitation,